Ancestry of Improved Cultivars of Asian Rice - Hargrove, Thomas R.; Coffman, W.R.; Cabanilla, Victoria L. (Wiley, 1980)
The 1970 attack of southern corn leaf blight (Helminthosporium maydis, Nisik and Miy.) was conditioned by cytoplasmic uniformity in the U.S. maize (Zea mays L.) crop. Researchers at the International Rice Research Institute (IRRI) studied the genetic diversity of improved Asian cultivars of rice (Oryza sativa L.), focusing on their maternal ancestry because cytoplasmically controlled traits are inherited through the female parents.All cultivars released by late 1979 under the IR designation trace to the same maternal parent ‘Cina,’ which indicates they might carry similar cytoplasm. Cina is the ultimate maternal parent of 62% of the post‐‘IR8’ cultivars in Bangladesh; 22% in India; 74% in Indonesia; 60% in Korea; 75% in Sri Lanka; and 25% in Thailand. More than half of the Philippines' riceland is planted to maternal derivatives of Cina. Among 79 entries from 10 nations and IRRI in the 1978 International Rice Yield Nursery, 59% trace their maternal ancestry to Cina. From 36 to 92% of the elite materials in other nurseries and IRRI screening trials derive from Cina. Of the 20,000 hybridizations made at IRRI by 1979, 44% of the female parents can be traced to Cina but the trend is declining.All named IR cultivars, except ‘IR5,’ and virtually all semidwarfs developed in national programs, carry the dwarfing gene from the Chinese dwarf cultivar ‘Dee‐geowoo‐gen.’The cytoplasmic similarity of modern cultivars, while posing no immediate practical problem, is of sufficient relevance to demand a prompt broadening of the maternal genetic base of improved rice cultivars. Recommendations are made for diversifying the maternal origin and the genetic base of subsequent semidwarfs.